Inverted Pendulum Nonlinear Controllers Using Two Reaction Wheels: Design and Implementation - Trentin, João Francisco Silva [UNESP]; Da Silva, Samuel [UNESP]; De Souza Ribeiro, Jean Marcos [UNESP]; Schaub, Hanspeter (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Reaction wheels have been extensively used to control and stabilize a wide range of applications due to the angular momentum exchange that they provide to mechanical systems. However, there exist several limitations associated with actuator saturation and the presence of singularities that lead towards the use of different controllers and devices. Recently, a new and unusual configuration using two reaction wheels was proposed and illustrated in an inverted pendulum to drive and control it using a simple and well-known PID controller. In this context, this paper improves the previous results on the same system by proposing two more sophisticated nonlinear controllers: a nonlinear proportional-derivative and a sliding mode controller. The proof of the stability of each controller is also provided, and the asymptotic stability is proven. A friction model is experimentally updated into the differential equations of the pendulum and also included for the controllers designing. A real-time application verifies the performance of the controllers using low-cost hardware. Results based on the analysis of different performance indices highlight the improvement of applying these two nonlinear control techniques comparing to the previous paper using this configuration of actuators.
Keywords: Inverted pendulum; low-cost hardware; reaction wheels; sliding mode control